2010
DOI: 10.1097/brs.0b013e3181d79f02
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging and Electromyography to Measure Lumbar Back Muscle Activity

Abstract: Both muscle functional MRI and EMG have specific (dis-) advantages and therefore have to be seen as complementary techniques. Nevertheless, our results support the validity of each method and indicate that MRI and EMG can be used independently to quantify lumbar muscle activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 29 publications
3
64
0
Order By: Relevance
“…1,35,37,38,40,62 In fact, innovative uses for advanced MRI applications may become particularly helpful in assessing the structure and function of spinal tissues (eg, muscles and intervertebral discs) and their physiological response to commonly prescribed physical therapy techniques. 16,23,31,32,38,46,70 These will be discussed in more detail in the cervical, thoracic, and lumbar spine sections.…”
Section: The Pearls and Pitfalls Of Magnetic Resonance Imaging For Thmentioning
confidence: 99%
See 1 more Smart Citation
“…1,35,37,38,40,62 In fact, innovative uses for advanced MRI applications may become particularly helpful in assessing the structure and function of spinal tissues (eg, muscles and intervertebral discs) and their physiological response to commonly prescribed physical therapy techniques. 16,23,31,32,38,46,70 These will be discussed in more detail in the cervical, thoracic, and lumbar spine sections.…”
Section: The Pearls and Pitfalls Of Magnetic Resonance Imaging For Thmentioning
confidence: 99%
“…[34][35][36][37] Such investigations, using both structural and advanced imaging sequences, have demonstrated changes in the structure and function of the deep and superficial lumbar muscles (multifidus, transverse abdominis, and erector spinae group) with ultrasound, CT, and MRI. 28,32,[55][56][57]65 Kader et al 62 have demonstrated a correlation between leg pain and MRI findings of increased atrophy and fatty infiltration of the ipsilateral lumbar multifidus, and others have demonstrated delayed and reduced recruitment of paraspinal muscles in response to functional tasks in patients with low back pain. 32,53,57,92 These findings have formed the foundation for clinical interventions that have shown to reduce painful symptoms.…”
Section: Emerging Evidence In Support Of Advanced Imaging Findings Ofmentioning
confidence: 99%
“…These different results may be due to differences in the test performance, or to the use of different measurement methods. Although both fMRI results and deformation values obtained from speckle tracking have shown a relationship with electrical muscle activity, 14,25 and speckle tracking results also show a linear relationship with maximal voluntarily contraction, 14 results from the two methods cannot be equalized as the degree of force used.…”
Section: Ventral Neck Musclesmentioning
confidence: 97%
“…Clinicians and researchers in our field have published and continue to publish seminal and oftentimes multidisciplinary works related to imaging. 6,8,9,[12][13][14][15][16]23,24,[26][27][28] Our journals continue to publish more imaging-related studies/cases, and our professional conferences encourage and accept poster and platform submissions that feature imaging. Finally, the recent development of the Special Interest Group on Imaging within the Orthopedic Section of the APTA is another important contribution to developing practice competencies, reducing practice variability, fostering imaging curriculum in physical therapist education, and promoting the role of the physical therapist, as a primary care team member, in judicious referral for imaging procedures.…”
Section: Towards a New Normative Model For Physical Therapist Practice Imentioning
confidence: 99%